2009
DOI: 10.1021/jp8109918
|View full text |Cite
|
Sign up to set email alerts
|

Inelastic Neutron Scattering Study of Confined Surface Water on Rutile Nanoparticles

Abstract: The vibrational density of states (VDOS) for water confined on the surface of rutile-TiO(2) nanoparticles has been extracted from low temperature inelastic neutron scattering spectra. Two rutile-TiO(2) nanoparticle samples that differ in their respective levels of hydration, namely TiO(2) x 0.37 H(2)O (1) and TiO(2) x 0.22 H(2)O (2) have been studied. The temperature dependency of the heat capacities for the two samples has been quantified from the VDOS. The results from this study are compared with previously… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

12
66
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 52 publications
(79 citation statements)
references
References 44 publications
(76 reference statements)
12
66
0
Order By: Relevance
“…The dynamical behaviour of interfacial water with TiO 2 and SiO 2 has been probed by various spectroscopic methods [11][12][13][14][15] including neutron scattering (inelastic, quasielastic and backscattering) and infrared spectroscopy. Attenuated Total Reflection-Infrared (ATR-IR) spectroscopy has been used to monitor the growth of different water layers on a SiO 2 surface.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The dynamical behaviour of interfacial water with TiO 2 and SiO 2 has been probed by various spectroscopic methods [11][12][13][14][15] including neutron scattering (inelastic, quasielastic and backscattering) and infrared spectroscopy. Attenuated Total Reflection-Infrared (ATR-IR) spectroscopy has been used to monitor the growth of different water layers on a SiO 2 surface.…”
Section: Introductionmentioning
confidence: 99%
“…Attenuated Total Reflection-Infrared (ATR-IR) spectroscopy has been used to monitor the growth of different water layers on a SiO 2 surface. 16 Quasi-elastic neutron scattering experiments have been used to study confined surface water in different materials 11,17 evaluating the vibrational density of states (VDOS), which can be used for the characterisation of the strength of hydrogen bonds, 16 providing information about the mobility of this interfacial water. However, information of local H-bond dynamics (formation and breaking) cannot be obtained with these techniques.…”
Section: Introductionmentioning
confidence: 99%
“…This is particularly true where hydrogen-bonded molecules play an important role in stabilising solutes via solvent interactions and forming "cages". Although TiO 2 is one of the most studied metal oxides in the literature, there is somewhat limited understanding of interfacial water molecules' behaviour on TiO 2 , despite recent progress in this area. 1 The dynamical behaviour of interfacial water molecules at titania surfaces has been probed recently by various spectroscopic methods.…”
Section: Introductionmentioning
confidence: 99%
“…1 The dynamical behaviour of interfacial water molecules at titania surfaces has been probed recently by various spectroscopic methods. [2][3][4][5][6] Quasi-elastic neutron scattering (QENS) 4 experiments have shown that hydrogen bonding between the first and second layers of water molecules above rutile-(110) surface stabilise the first monolayer at the interface, providing a less mobile and more ice-like structure quite distinct from that of liquid water. Neutron backscattering experiments, along with molecular dynamics (MD) 7 studies have shown that detailed hydrogen bonding properties depend on the level of hydration and its dynamical correlation with diffusion and stability.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation